Peak running intensities in field hockey - a positional analysis - Dewar, H.; Clarke, J. (Journal of Human Kinetics, 2021)
The aim of this study was to investigate the positional mean peak running periods during a field hockey match using a moving average method. The secondary aim was to investigate how the peak periods changed between quarters and playing positions. The moving average method was used to analyse the data because of the nature of field hockey, which has natural fluctuations of high and low intensity periods of play. The time periods included periods from 1 to 10 minutes. The level of significance for results was set at p = 0.05. The study found that forwards had a peak running intensity of 194 ± 24.2 m·min -1, midfielders 189 ± 11.9 m·min -1, and defenders 182.6 ± 17.9 m ·min -1. These results showed that forwards had the highest maximum running speed, with defenders having the lowest one (p = 0.0025). Additionally, running output started to plateau after 7/8-min periods for each of the three positions. Forwards did not show any statistically significant changes across the four quarters. Midfielders showed effect sizes ranging from >0.6 to >2.0 (moderate, large and very large) si gnificance when comparing the first three quarters to the fourth one. Defenders showed >0.6 to <2.0 (moderate to large) effect sizes to occur when comparing the first and second quarter to the fourth. There are three main practical implications from the results of this study: 1) th e creation of conditioning drills, 2) substitution patterns, and 3) knowledge to be able to plan and train at or above peak match demands.